Pseudoprogression after advanced first-line endocrine therapy in metastatic breast cancer with bone metastasis: A case report - Tian, Aijuan; Lv, Huiyun; Liu, Wei; Zhao, Jinbo; Zhao, Shanshan; Wang, Kainan; Song, Chen (Frontiers in Oncology, 2023)
Approximately 75% of patients with advanced breast cancer develop bone metastasis, which significantly affects both the quality of life and the survival rate of patients. Accurate determination of the status of bone metastases is important for developing treatment strategies and the prognosis of the disease. Here, we report the case of a 33-year-old patient with advanced metastatic breast cancer (MBC) and multiple bone metastases, in which advanced first-line endocrine therapy and second-line chemotherapy were both considered unsuccessful according to the efficacy evaluation by conventional imaging. Considering the possibility of bone pseudoprogression, the original endocrine scheme was reapplied, and bone metastases achieved a great response of non-complete response (CR)/non-progressive disease (PD). This case showed that, in the course of therapy for the disease, if bone scintigraphy (BS) shows increased lesion density or new lesions, this probably indicates a favorable response (osteoblastic repair of osteolytic lesions) to therapy, and not the worsening of metastatic lesions, called bone pseudoprogression. This paper will provide new insights into strategies for the treatment of bone metastasis and shows the significance of distinguishing osteoblastic bone repair from real bone lesion progression in clinical settings.